2023
DOI: 10.1186/s12933-023-01748-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of coronary artery disease in patients with type 2 diabetes mellitus based on computed tomography and pericoronary adipose tissue radiomics: a retrospective cross-sectional study

Abstract: Background Patients with type 2 diabetes mellitus (T2DM) are highly susceptible to cardiovascular disease, and coronary artery disease (CAD) is their leading cause of death. We aimed to assess whether computed tomography (CT) based imaging parameters and radiomic features of pericoronary adipose tissue (PCAT) can improve the diagnostic efficacy of whether patients with T2DM have developed CAD. Methods We retrospectively recruited 229 patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Previous studies have established that RCA-FAI was markedly elevated in patients with T2DM as opposed to those without, and this holds true irrespective of the degree of arterial stenosis or the vulnerability of plaque formations [6] . Further investigation focusing on individuals with T2DM has highlighted that the effectiveness of RCA-FAI in identifying coronary artery disease was more representative than the Left anterior descending (LAD) and Left circum ex (LCX) arteries, making it a better diagnostic tool for coronary artery disease in T2DM patients [20] . Additionally, RCA-FAI has been identi ed as an independent prognostic factor for the onset of microvascular complications in T2DM patients [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established that RCA-FAI was markedly elevated in patients with T2DM as opposed to those without, and this holds true irrespective of the degree of arterial stenosis or the vulnerability of plaque formations [6] . Further investigation focusing on individuals with T2DM has highlighted that the effectiveness of RCA-FAI in identifying coronary artery disease was more representative than the Left anterior descending (LAD) and Left circum ex (LCX) arteries, making it a better diagnostic tool for coronary artery disease in T2DM patients [20] . Additionally, RCA-FAI has been identi ed as an independent prognostic factor for the onset of microvascular complications in T2DM patients [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Among the studies conducted on the relationship between PCAT and the clinic, most studies focused on the correlation between PCAT and ACS or CHD ( 2 , 21 , 22 ). Clinical risk factors combined with CT-based imaging parameters and PCAT radiomic features in patients with type 2 diabetes showed that this model effectively diagnosed CHD in patients with type 2 diabetes ( 21 ). A cross-sectional study showed that the mean PCAT attenuation values were correlated with plaque parameters and the degree of stenosis in patients with ACS ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have established that RCA-FAI was markedly elevated in patients with T2DM as opposed to those without, and this holds true irrespective of the degree of arterial stenosis or the vulnerability of plaque formations [ 6 ]. Further investigation focusing on individuals with T2DM has highlighted that the effectiveness of RCA-FAI in identifying coronary artery disease was more representative than the LAD and LCX arteries, making it a better diagnostic tool for coronary artery disease in patients with T2DM [ 23 ]. Additionally, RCA-FAI has been identified as an independent prognostic factor for the onset of microvascular complications in patients with T2DM [ 24 ].…”
Section: Discussionmentioning
confidence: 99%